Does the Use of Learning Management Systems With Hypermedia Mean Improved Student Learning Outcomes? - Sáiz-Manzanares, María Consuelo; Marticorena-Sánchez, Raúl; Díez-Pastor, José Francisco; García-Osorio, César Ignacio (Frontiers in Psychology, 2019)
Learning Management Systems (LMS) that incorporate hypermedia Smart Tutoring Systems and personalized student feedback can increase Self-Regulated Learning (SRL), motivation, and effective learning. These systems are studied with the following aims: 1) to verify whether the use of LMS with hypermedia Smart Tutoring Systems improves student learning outcomes; 2) to verify whether the learning outcomes will be grouped into performance clusters (Satisfactory, Good, and Excellent); and, 3) to verify whether those clusters will group together the different learning outcomes assessed in four different evaluation procedures. Use of the LMS with hypermedia Smart Tutoring Systems was studied among students of Health Sciences, all of whom had similar test results in the use of metacognitive skills. It explained 38% of the variance in student learning outcomes in the evaluation procedures. Likewise, three clusters that grouped the learning outcomes in relation to the variable ‘Use of an LMS with hypermedia Smart Tutoring Systems vs. No use’ explained 60.4% of the variance. Each cluster grouped the learning outcomes in the different evaluation procedures. In conclusion, LMS with hypermedia Smart Tutoring Systems in Moodle increased the effectiveness of student learning outcomes, above all in the individual quiz-type tests. It also facilitated personalized learning and respect for the individual pace of student-learning. Hence, modules for the analysis of supervised, unsupervised and multivariate learning should be incorporated into the Moodle platform to provide teaching tools that will undoubtedly contribute to improvements in student learning outcomes.